2020
DOI: 10.7150/thno.47893
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mesenchymal stem cell proteomes in situ in the ischemic heart

Abstract: Rationale: Cell therapy for myocardial infarction is promising but largely unsuccessful in part due to a lack of mechanistic understanding. Techniques enabling identification of stem cell-specific proteomes in situ in the injured heart may shed light on how the administered cells respond to the injured microenvironment and exert reparative effects. Objective: To identify the proteomes of the transplanted mesenchymal stem cells (MSCs) in the infarcted my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…The change of ribosomal proteins to ischemic insults has been shown to persist for up to 14 days. We demonstrated that the increased expression of RPL28 and RPL26 at days 1 and 3 postsurgery, consistent with other reports (Lee et al, 2013;Ong et al, 2013;Han et al, 2020), and elevations declined to normal values by day 14. RPL28 belongs to the ribosomal proteins family.…”
Section: Proteomic Changes Of Mscs From Hli In Muscle Tissuesupporting
confidence: 92%
See 3 more Smart Citations
“…The change of ribosomal proteins to ischemic insults has been shown to persist for up to 14 days. We demonstrated that the increased expression of RPL28 and RPL26 at days 1 and 3 postsurgery, consistent with other reports (Lee et al, 2013;Ong et al, 2013;Han et al, 2020), and elevations declined to normal values by day 14. RPL28 belongs to the ribosomal proteins family.…”
Section: Proteomic Changes Of Mscs From Hli In Muscle Tissuesupporting
confidence: 92%
“…Flow cytometry was performed as we previously described ( Han et al, 2020 ). Briefly, BMSCs cells were digested by trypsin and collected by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, when exosomes produced by the MetRS* MSCs were systemically administered to mice, the protein components of their cargo could be accurately and reliably tracked, visualized, identified, and quantified in tissues from a variety of organs, including both intact and infarcted hearts. Notably, as bioorthogonal chemistry can occur in living systems without disrupting native biochemical processes ( Prescher et al, 2004 ; Prescher and Bertozzi, 2005 ; Sletten and Bertozzi, 2011 ; Ngo et al, 2013 ; Han et al, 2020a ), this approach can be applied to other cell populations and even extended to wholly in vivo investigations by generating MetRS ∗ -transgenic mice ( Alvarez-Castelao et al, 2017 ; Han et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%